2018
DOI: 10.1111/ele.12925
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal patterns of herbivore pressure in a temperate herb support the biotic interactions hypothesis

Abstract: The longstanding biotic interactions hypothesis predicts that herbivore pressure declines with latitude, but the evidence is mixed. To address gaps in previous studies, we measured herbivory and defence in the same system, quantified defence with bioassays, and considered effects of leaf age. We quantified herbivory and defence of young and mature leaves along a continental gradient in eastern North America in the native herb Phytolacca americana L. Herbivory in the field declined with latitude and was strongl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 65 publications
5
65
4
Order By: Relevance
“…It is not clear, however, to what extent the turnover of network structure is driven by a systematic change in species composition or of pairwise interactions (Poisot et al 2012(Poisot et al , 2015. We know that interactions vary with the environment in other systems, for instance, herbivory (Shurin et al 2012, Baskett et al 2018) and predation (McKinnon et al 2010, Legagneux et al 2014 are often found to increase with temperature, resulting in spatial variation of trophic cascades (Gray et al 2016). Further, the occurrence of interactions among host and parasite is highly stochastic even when both are present, and not predictable by the variables considered by us.…”
Section: Perspectivesmentioning
confidence: 99%
“…It is not clear, however, to what extent the turnover of network structure is driven by a systematic change in species composition or of pairwise interactions (Poisot et al 2012(Poisot et al , 2015. We know that interactions vary with the environment in other systems, for instance, herbivory (Shurin et al 2012, Baskett et al 2018) and predation (McKinnon et al 2010, Legagneux et al 2014 are often found to increase with temperature, resulting in spatial variation of trophic cascades (Gray et al 2016). Further, the occurrence of interactions among host and parasite is highly stochastic even when both are present, and not predictable by the variables considered by us.…”
Section: Perspectivesmentioning
confidence: 99%
“…, Anstett et al. , Baskett and Schemske ). For example, a meta‐analysis found that the latitudinal diversity gradient is stronger in studies that cover a wider latitudinal range, although latitudinal midpoint did not affect the strength of the gradient (Kinlock et al.…”
Section: Introductionmentioning
confidence: 97%
“…This approach is commonly used to study plant–herbivore interactions (Pennings and Silliman , Salgado and Pennings , Anstett et al. , , Baskett and Schemske ), but has found mixed support for the biotic interactions hypothesis (Moles et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Mittelbach et al, ; but see: Schluter & Pennell, ) could obfuscate patterns in our data if sister clades consistently differ in their regional associations. Previous work by Lewinsohn () found that latex is more common and more abundant in tropical plant species and herbivory pressures have been shown to be higher in the tropics (Baskett & Schemske, ; Coley & Barone, ). A cursory post‐hoc examination of the clades in this analysis, in which we evaluated whether sister clade status is confounded with tropicality, did not reveal a detectible signal of strong latitudinal differences across clades (Figure ).…”
Section: Discussionmentioning
confidence: 99%